KNOWLEDGE AND ATTITUDES OF TEENAGE GIRL WITH PATHOLOGICAL VAGINAL DISCHARGE PREVENTION IN STATE 1ST HIGH SCHOOL TAKALAR DISTRICT - Mustika Ramadhanti; Hasnah M. Noor; Marsuki Marsuki (Media Kesehatan Politeknik Kesehatan Makassar, 2019)
Leukorhea is a liquid secretion from the female genitals that is experienced by every woman who is physiological. Physiological leukorhea can be a pathological or abnormal condition that can be caused by various factors, namely bacteria, viruses, or fungi. This study aims to determine the relationship of knowledge and attitudes of teenage girl with prevention of pathological vaginal discharge in State 1ST High school, Takalar District, with a cross sectional methodeThe subjects of this study were all student of class X in state 1ST high school, Takalar District, as many as 63 respodents. The research design uses a Non ProbabilitySampling technique. The statistical analysisi used in this study was the chi-square statistic, with confidence interval α=0,05.The results showed that the significant value of knowledge ρ=0,000 (ρ<0,05) with a coefficient value (Phi = 0,810), attitude ρ=0,000 (ρ=0,725). So that it can be concluded that there is a relationship between the knowledge and attitudes of teenage girl with the prevention pf pathological vaginal discharge in State 1ST High School, Takalar District. Therefore, it its expected that teenage girl will read more about references to vaginal discharge to that the can open their horizons on how to prevent pathological vaginal discharge so that it does not affect them in the future.